Comparison of Algorithms of Individual and Group Behavior - Kopsov, Igor (Advances in Social Sciences Research Journal, 2021)
It has been suggested that the functionality of matter, life, and mind can be described by algorithms containing a sequence of steps and feedback mechanisms. Social processes were until now not considered. Consequently, we examine algorithms of behavior of groups of various kinds, identify their common parameters, and undertake a comparative analysis to the algorithm of individual behavior. We conclude, that despite some application-specific differences, groups operate in accordance with a unified algorithm and, furthermore, this algorithm is the same as the generic algorithm of individual behavior. We demonstrate that in the generally perceived progression matter-life-mind-culture/society, the latter transition cannot be validated. Homogeneity of algorithms of individual and group behavior leads to the proposition that the human mind/psyche and social processes belong to the same level of complexity of nature. This challenges the commonly held perception that society/culture is a standalone perspective of reality separate from the mind.